The Effect Of Psychoeducation Based On Self Care Theory On Knowledge, Compliance, Independent Care And Blood Glucose Levels In Patients With Type 2 Diabetes Mellitus - Arief Candra Permana; Eppy Setiyowati; Chilyatiz Zahroh (Poltekkes Kemenkes Surakarta, 2022)
Background: The style of modern society in dietary habits such as eating foods that are high in fat, sugar and frequent attendance at receptions or parties, tends to consume excessive food which can lead to an increase in blood sugar levels. The purpose of this study was to analyze the effect of psychoeducation based on self-care theory on knowledge, compliance, independent care and blood glucose levels in patients with type 2 diabetes mellitus. Methods: This type of research uses a researched method that is an exploratory approach. In the first stage the type of descriptive qualitative research with a case study approach and in the second stage using a Quasy-Experimental research design with a pre posttest approach. Samples were taken using the simple random sampling method of 6 participants in stage I and stage II totaling 64 respondents consisting of 32 intervention groups and 32 control groups. The independent variable is psychoeducation based on self-care theory. Variables between knowledge, compliance, independent care. The dependent variable of blood glucose levels. The instrument uses interviews, knowledge, compliance questionnaires, glucometers and modules. The analysis used the MANOVA test with a significant value of = 0.05. Results: Research in the first stage obtained 4 themes, namely knowledge, self-motivation, social motivation, behavioral skills. The results of the second stage of the study showed that there was an effect of psychoeducation based on self-care theory on knowledge (p=0.000), compliance (p=0.000), self-care independence (p=0.000), and blood glucose levels (p=0.000). Conclusion: This intervention can be given to improve the quality of patient's health.